A preliminary study of tuna fishing gears in Jolo and vicinity - Aure, Romulo C. (Diliman, Quezon City College of Fisheries, University of the Philippines, 1969)
The tuna fishing gears owned and operated by the natives of Jolo and vicinity are varied in form and method. The rampant, though illegal, use of dynamite is the most efficient in terms of catch per unit of effort, without considering the dangers involved and wasteful effect on the marine environment. The fish corrals are comparatively the most laborious and complicated among the gears observed. They are effective in catching schools of tuna since a system of barriers and net is used for impounding fish. This is an obvious advantage over the simper method of using hooks and lines. Handlining at night utilizing light for attracting fish hooks the bigger yellowfin tuna, while trolling catches the smaller tuna. This paper describes the method and operation of these different tuna fishing gears and attempts to compare their efficiency according to catch per unit of effort considering the average daily amount of catch, hours of operation, and manpower utilized. The prospectus for each gear and some of the problems of the fishermen are also presented here.
Thesis (Undergraduate. Bachelor of Science in Fisheries) College of Fisheries, University of the Philippines, 1969..
Keywords: Tuna; Fishing gears